Gain-of-function of TRPM4 predisposes mice to psoriasiform dermatitis - Yamada, Daisuke; Vu, Simon; Wu, Xuesong; Shi, Zhenrui; Morris, Desiree; Bloomstein, Joshua D.; Huynh, Mindy; Zheng, Jie; Hwang, Samuel T. (Frontiers in Immunology, 2022)
Transient receptor potential melastatin 4 (TRPM4) is a Ca2+-activated, monovalent cation channel that is expressed in a wide range of cells. We previously reported two gain-of-function (GoF) mutations of TRPM4 as the cause of progressive symmetric erythrokeratodermia (PSEK), which shares similar clinical and histopathological features with psoriasis. Using CRISPR/Cas9 technology, we generated TRPM4I1029M mice that have the equivalent mutation to one of the two genetic mutations found in human PSEK (equivalent to human TRPM4I1033M). Using this mutant mice, we examined the effects of TRPM4 GoF at the cellular and phenotypic levels to elucidate the pathological mechanisms underlying PSEK. In the absence of experimental stimulation, TRPM4I1029M mice did not show a phenotype. When treated with imiquimod (IMQ), however, TRPM4I1029M mice were predisposed to more severe psoriasiform dermatitis (PsD) than wild-type (WT), which was characterized by greater accumulation of CCR6-expressing γδ T cells and higher mRNA levels of Il17a. In TRPM4I1029M mice, dendritic cells showed enhanced migration and keratinocytes exhibited increased proliferation. Moreover, a TRPM4 inhibitor, glibenclamide, ameliorated PsD in WT and TRPM4I1029M mice. Our results indicate elevated TRPM4 activities boosted susceptibility to cutaneous stimuli, likely through elevation of membrane potential and alteration of downstream cellular signaling, resulting in enhanced inflammation. Our results further suggest a possible therapeutic application of TRPM4 inhibitors in psoriasis.